(untitled) (MAUSAM, 1984)
Droughts have been a matter of serious concern to man since ancient times, and 55, The water balance even today they are an outstanding example of man’s helplessness before nature’s large-scale and formidable phenomena. To the meteorologist, drought is a rainless situation for an extended period of time during which some precipitation should have been normally received depending upon the geographical location of the region and season of the year. To the agriculturist, drought is a shortage of moisture availability for his crops while the hydrologist views it as being responsible for depression of surface and sub-surface water levels or decrease of stream flow. Most of the concepts and definitions suggested in literature are based on techniques which either lack physical basis or are empirical. However, Thornthwaite for the first time suggested that water availability or its deficiency should always be considered in relation to the water need of the region taking into consideration the important role of soil moisture, for a rational understanding of droughts. In this paper, the index of moisture adequacy (Ima)derived from water balance procedures, has been employed to categorize droughts from the agricultural and ecological point of view. Droughts of selected stations in the semi-arid zone of India have been analyzed. However, more important than the delineation of drought years of various severities, is the assessment of the exact duration of drought spells. Selected drought spells were, therefore, analyzed critically by plotting the ratio of the departures of monthly indices of moisture adequacy (Ima) from the climatic normal, to the standard deviation of (Ima) for that month. This technique is found to be of great value in agricultural and ecological investigations as due weightage is given to the drought resistance and tolerance of crops which are adapted to the region. It also highlights the fact that the same amount of water deficiency during the various seasons of the year and at different stages of crop growth causes varying moisture stress. This is of special interest in tropical regions where it is the moisture factor that inhibits the growth of vegetation to its potential levels.